TINJAUAN LITERATUR: KEBUTUHAN ORANG TUA DENGAN BAYI SAKIT KRITIS DALAM IMPLEMENTASI FAMILY CENTERED CAREDI RUANG PERAWATAN INTENSIF NEONATAL - Hendrawati, Sri; Maryam, Nenden Nur Asriyani; Permana, Septa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Infant hospitalization in the neonatal intensive care unit adversely affects both infants and their parents. Efforts can be developed to minimize the negative impact by applying family-centered care. The first step is to identify the needs of parents. Therefore, this literature review aims to identify the needs of parents with critically ill infants in the neonatal intensive care unit. Articles were collected through EBSCOhost, PubMed, Science Direct, and Scopus electronic database using the keywords critically ill infants, family-centred care, needs of parents, and neonatal intensive care unit were searched for qualitative and quantitative studies. The articles reviewed were only articles with full text, written in English, and published from 2015 to 2024. It found 925 articles on infant care in the neonatal intensive care unit, only 10 articles explicitly related to the needs of parents. Needs of parents with critically ill infants, including the needs for (1) positive acceptance and caring attitude of nurses towards infant and parents; (2) accurate information, effective communication, and involvement of parents in decision-making regarding the condition of the infant; (3) feel confident and believe that infant gets the best care; (4) have adequate contact with an infant; (5) involved in caring for the infant with the guidance and supervision of nurses; and (6) comfortable neonatal intensive care unit environment. According to the six needs, each parent has a different priority. Identifying the needs of parents in the neonatal intensive care unit can allow nurses to integrate these needs into family-centered care so that parents can meet these needs, get satisfaction, and improve the quality of life of infants